2016
DOI: 10.3892/ol.2016.4939
|View full text |Cite
|
Sign up to set email alerts
|

miR-101 inhibits glioma cell invasion via the downregulation of COX-2

Abstract: Glioma is the most common type of primary tumor of the central nervous system. The present study aimed to demonstrate the role of miR-101 and cyclooxygenase-2 (COX-2) in the initiation and development of glioma. The expression of miR-101 and COX-2 in normal and malignant human glial cells and tissues was determined by western blotting and quantitative polymerase chain reaction analysis. The role of miR-101 on COX-2 expression was evaluated by a dual-luciferase reporter assay. The effects of miR-101 and COX-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Accumulating evidence revealed that miRNA regulate several cancer‐related processes during tumorigenesis through binding to the 3′UTR of the target genes (Nugent, ; Tsai et al ., ). Furthermore, miR‐101 was considered to regulate cell proliferation, angiogenesis, invasion, and migration in many types of tumors and serve as a tumor suppressor (Li et al ., ; Liu et al ., ; Ma et al ., ). In this study, we showed that extracellularly applied S1P or overexpressing SphK1 inhibit miR‐101 expression in human chondrosarcoma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence revealed that miRNA regulate several cancer‐related processes during tumorigenesis through binding to the 3′UTR of the target genes (Nugent, ; Tsai et al ., ). Furthermore, miR‐101 was considered to regulate cell proliferation, angiogenesis, invasion, and migration in many types of tumors and serve as a tumor suppressor (Li et al ., ; Liu et al ., ; Ma et al ., ). In this study, we showed that extracellularly applied S1P or overexpressing SphK1 inhibit miR‐101 expression in human chondrosarcoma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Acidity was suggested to be associated with the induction of pro-inflammatory factors, such as TNF-α, IL-1β, and IL-6 [36], and COX2-dependent inflammatory responses [37]. Overexpression of COX2 has been suggested to be related to invasion in several types of cancer cells, including glioma and breast cancer cells [38,39], and inhibition of COX2 was shown to reduce lymphatic metastasis of a human gastric cancer cell line in xenografts [40]. Ellagic acid has been shown to exert anti-inflammatory activity in several disease models and decrease COX2-triggered exacerbation of inflammation [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant glioma is the most common malignant tumor of the central nervous system [ 1 ]. The invasive performance and easy transformation from lower grades to higher grades were the main causes of the poor prognosis of glioma [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%